Digital Logistics Transformation for Operational and Financial Performance - Widyawan, Gerardio Septa; Maniah, Maniah; Mulyati, Erna (Dinasti Publisher, 2026)
Digital transformation in the logistics sector is crucial for improving operational performance and financial outcomes, especially amid the rapidly growing demands of Indonesia’s economy and the global market. This study examines the impact of digital logistics transformation and related factors, including top management commitment, IT capability, employees’ digital mindset and skills, work culture change, human capital capacity, as well as the operational and financial performance of PT Pos Indonesia (Persero). Using a quantitative approach with data collected from 91 senior leaders at PT Pos Indonesia and analyzed through SmartPLS, the study proves that digital transformation significantly enhances both operational and financial performance. The factors that contribute most positively to the success of digital transformation are IT capability, employees’ digital mindset, and human capital capacity. In contrast, top management commitment, individual digital skills, and work culture change did not show a direct significant impact at the early stage. Nevertheless, digital transformation was found to be a strong mediating variable in linking internal company factors with performance improvement. This confirms that digital strategies are not merely technological innovations but also concrete mechanisms for creating business value and strengthening the company’s competitiveness in the logistics industry.